Participation of primary care nurses in the prevention of chronic non-communicable diseases in the republic of Kazakhstan: A cross-sectional study - Alexandra Masharipova; Nasikhat Nurgaliyeva; Gulmira Derbissalina (Wolters Kluwer Medknow Publications, 2023)
Background: Chronic diseases are a huge threat to public health in Kazakhstan and around the world. Many deaths can be prevented by using evidence-based behavioral interventions. Nurses, as the most numerous health care workers, can perform behavioral therapy for the prevention of Non-Communicable Diseases (NCDs). This study was conducted in order to explore the behavioral interventions performed by nurses, to analyze current problems, barriers and the attitude of nurses to these activities. Materials and Methods: A cross-sectional study was conducted among 260 nurses in the city of Nur-Sultan from 2019 to 2020. The sample was calculated using a formula and simple random sampling. The study was conducted using a specially compiled questionnaire. Descriptive statistics were chosen as a statistical method. Pearson's Chi-square criterion was used to identify a statistically significant relationship between variables. Results: Among 260 nurses, 208 participants (80%) had the desire to conduct behavioral interventions among patients. Most nurses do not have enough time to conduct behavioral interventions. A short work experience affects to a greater extent nurses use passive training methods. Almost half (47.30%) of nurses rate their level of knowledge about the real effects of drugs, tobacco, alcohol, and preventive measures on the body as "average". Conclusions: The work of nurses on the prevention of NCDs is not performed enough due to lack of working time and available domestic literature, heavy workload. Behavioral therapy should be based on reliable scientific evidence, which can be achieved through the development of clinical guidelines and continuous training of nurses.